2012
DOI: 10.1227/neu.0b013e31822ec2b0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 5 Inhibition Attenuates Cerebral Vasospasm and Improves Functional Recovery After Experimental Subarachnoid Hemorrhage

Abstract: Background Cerebral vasospasm is an independent predictor of poor outcome after subarachnoid hemorrhage (SAH). The nitric oxide-cyclic GMP (NO-cGMP) vasodilatory pathway is strongly implicated in its pathophysiology. Preliminary studies suggest that phosphodiesterase 5 (PDE5) – an enzyme that degrades cGMP – may play a role, as the PDE5 inhibitor sildenafil was found to reduce vasospasm after SAH. However, several questions that are critical when considering translational studies remain unanswered. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 34 publications
2
35
1
1
Order By: Relevance
“…In addition, perfusion was examined in vivo, whereas vasospasm was analyzed ex vivo. The time point of 72 h was chosen because our data and other studies have reported that vasospasm peaks 72 h after induction of SAH in the murine endovascular filament perforation model [16,23,24]. Although we cannot rule out that a correlation between vasospasm and cortical perfusion may have been present at earlier time points, the lack of correlation at 72 h indicates that large vessel vasospasm is of limited relevance in the murine model.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, perfusion was examined in vivo, whereas vasospasm was analyzed ex vivo. The time point of 72 h was chosen because our data and other studies have reported that vasospasm peaks 72 h after induction of SAH in the murine endovascular filament perforation model [16,23,24]. Although we cannot rule out that a correlation between vasospasm and cortical perfusion may have been present at earlier time points, the lack of correlation at 72 h indicates that large vessel vasospasm is of limited relevance in the murine model.…”
Section: Discussionmentioning
confidence: 98%
“…This time point was selected to determine the impact on cortical perfusion at the peak of CV [16,23,24]. We analyzed the vessel volume of a 2.5-mm vessel segment of the left MCA distal of the carotid T, which is a highly sensitive parameter for evaluating vasospasm [28].…”
Section: Sah Induces Vasospasmmentioning
confidence: 99%
See 1 more Smart Citation
“…Ballard et al suggested that sildenafi l also acts on PDE-1 and PDE-2, which are involved in controlling cerebral circulation ( 11 ). Studies on mice have demonstrated that sildenafi l decreases cerebral vasospasm by increasing and restoring cGMP levels ( 12 ). Th e reported adverse eff ects of sildenafi l include headache, visual disturbances, pupil-sparing third nerve palsy, and transient hypertension, and these symptoms suggest that sildenafi l also aff ects brain microvasculature regulation ( 13 , 14 ).…”
Section: Intracranial Aneurysm and Sildenafilmentioning
confidence: 99%
“…Based on available evidence (Garthwaite et al, 2006), it is likely that NO affects the function of HCN through cGMP gating of these channels. However, an increase in phosphodiesterase-5 activity and consequent decrease in cGMP occurs in cortical neurons after experimental SAH (Han et al, 2012). It is therefore possible that cGMP downregulation seen in vivo would further exacerbate the magnitude of HCN channel inhibition and thereby enhance the degree of neuronal excitability.…”
mentioning
confidence: 99%